Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Kinerja Karyawan Pada PT. Pegadaian (Persero) Kanwil 1 Medan dengan Kepuasan Kerja Sebagai Variabel Intervening - Fuad, Ahmad; Bahri, Syaiful; Tanjung, Hasrudy (CV. ITTC INDONESIA, 2023)
This research aims to determine the effect of compensation on job satisfaction at PT. Pegadaian (Persero) Regional Office I Medan, the influence of motivation on job satisfaction at PT. Pegadaian (Persero) Regional Office I Medan, to determine the effect of compensation on employee performance at PT. Pegadaian (Persero) Regional Office I Medan, knows the influence of motivation on employee performance at PT. Pegadaian (Persero) Regional Office I Medan, knows the effect of job satisfaction on employee performance at PT. Pegadaian (Persero) Regional Office I Medan, to determine the effect of compensation on employee performance with job satisfaction as an intervening variable at PT. Pegadaian (Persero) Regional Office I Medan, and to determine the effect of motivation on employee performance with job satisfaction as an intervening variable at PT. Pegadaian (Persero) Regional Office I Medan. The population in this study were all permanent employees at PT. Pegadaian (Persero) Regional Office I Medan as many as 49 people. Considering the small population above, the researcher used the entire population as a sample, where this research is called census research. Thus, the sample in this study was 49 permanent employees at PT. Pegadaian (Persero) Regional Office I Medan. The data collection technique in this research is a questionnaire. The data analysis techniques used are the classical assumption test, path analysis, t test, and F test and determinant coefficients. Based on the results of research tests conducted, it shows that the financing variable has a positive and significant effect on employee performance, the motivation variable has a positive and significant effect on employee performance. The dependency variable has a positive and significant effect on job satisfaction. The motivation variable has a positive and insignificant effect on job satisfaction. Job satisfaction is unable to mediate between motivation and employee performance. Job satisfaction is able to mediate between compensation and employee performance.